2005
DOI: 10.1021/jp044347q
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Distribution of a 14-Residue Peptide in Solution:  A Fluorescence Resonance Energy Transfer Study

Abstract: We demonstrate here that a nitrile-derivatized phenylalanine residue, p-cyanophenylalanine (Phe(CN)), and tryptophan (Trp) constitute a novel donor-acceptor pair for fluorescence resonance energy transfer (FRET). The Förster distance of this FRET pair was determined to be approximately 16 A and hence is well suited for determining relatively short separation distances. To validate the applicability of this FRET pair in conformational studies, we studied the conformational heterogeneity of a 14-residue amphipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
146
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(159 citation statements)
references
References 60 publications
11
146
1
1
Order By: Relevance
“…Studies on the unfolded states of polypeptides, as well as loop regions in folded proteins, have indicated that unfolded conformations are flexible and can be reasonably approximately as a random coil, with persistence lengths and effective bond lengths 3.81. 34,66 However, the ABZ-E 20 -YNO 2 persistence length of >5.2 Å in pH 6 and 7.2 Å in pH 9 adds to increasing evidence that many unfolded proteins and peptides systems are more extended than theoretical random coils (l p > 3.8 Å ). 2,7,8,13,58 A recent study found that the persistence length of a number of regions of the natively disordered protein a-synuclein ranged between 5.5-6.5 Å .…”
Section: E 20 Is Highly Extended At Ph 6 and Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the unfolded states of polypeptides, as well as loop regions in folded proteins, have indicated that unfolded conformations are flexible and can be reasonably approximately as a random coil, with persistence lengths and effective bond lengths 3.81. 34,66 However, the ABZ-E 20 -YNO 2 persistence length of >5.2 Å in pH 6 and 7.2 Å in pH 9 adds to increasing evidence that many unfolded proteins and peptides systems are more extended than theoretical random coils (l p > 3.8 Å ). 2,7,8,13,58 A recent study found that the persistence length of a number of regions of the natively disordered protein a-synuclein ranged between 5.5-6.5 Å .…”
Section: E 20 Is Highly Extended At Ph 6 and Phmentioning
confidence: 99%
“…11,13,14,[30][31][32][33] Many other studies have demonstrated that FRET is capable of measuring relatively small distance and distance distribution changes during conformational shifts in short peptide systems such as glycopeptide folding, glycosylation of peptide substrates, thermal stretching of unfolded peptides, zinc finger folding, hydrophobic peptide collapse, and a-helix denaturation. [16][17][18][19][20][21]34 However, to date, a detailed denaturation titration between a 100% a-helical peptide and a 0% helix random coil state has not been conducted using FRET to investigate the degree to which this transition is indeed a simple two-state transition or whether alternate conformations may exist. This is the objective of the present study.…”
mentioning
confidence: 99%
“…The GB1-m3 peptide was designed with a much better thermal stability than the parent GB1 peptide [70]. Tucker et al designed a new FRET pair on the GB1-m3 peptide by replacing the single Phe residue with a non-natural residue, Phe CN , where a cyano group is added at the para position of the Phe side chain [75]. The FRET pair is therefore formed between the Phe CN (donor) and the Trp (acceptor).…”
Section: Figmentioning
confidence: 99%
“…Recently, Jun et al (34) used electron spin resonance distance measurements to probe the distance of two spin labels attached to an alanine-based peptide in the folded and (thermally) unfolded states and found the respective value for the latter to be too short for a pure PPII state of the peptide. Analogously, Tucker et al (35) used an intrinsic FRET pair to deduce that the supposedly disordered mastoparan X peptide actually exists in aqueous solution as an ensemble of compact conformations.…”
mentioning
confidence: 99%